Analisis Retrospektif Penerapan Kapasitas Anaerobik Alaktasid dengan Metode Long Interval Training - Ida Yunani; Dikdik Zafar Sidik; Yopi Kusdinar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to retrospectively analyze the application of the long interval training method to increase athletes’ anaerobic alactate capacity. The study used a retrospective descriptive method with four athletes participating in a training program for 16 meetings, using the Dash Sprint instrument as a measure of explosive ability. Data were analyzed using descriptive statistics including the average, highest value, lowest value, range, and standard deviation. The results showed an average Dash Sprint time of 3.40 seconds, with the best result of 3.32 seconds and the lowest result of 3.50 seconds, and an average athlete attendance of 89.06%. The study findings indicate that the long interval training method has the potential to make a positive contribution to anaerobic alactate capacity, although performance results are also influenced by individual factors such as initial physical condition, sprint technique, and physiological responses of each athlete. In conclusion, long interval training can be used as a training method to support the improvement of sprint ability and anaerobic alactate capacity, especially in sports that require short-duration explosive activity. Keywords: Anaerobic Alactacid Capacity, Futsal Athletes, Long Interval Training